Proteomic Approach to the Potential Role of Angiotensin II in Barrett Dysplasia. Issue 4 (30th January 2019) - Bratlie, Svein Olav; Wallenius, Ville; Edebo, Anders; Fändriks, Lars; Casselbrant, Anna
Abstract : Background and Aim: Dysplasia in Barrett's esophagus (BE) is regarded as a preneoplastic lesion. The renin–angiotensin system (RAS), known for its role in electrolyte homeostasis and hemodynamics, has also been shown to have tissue‐based features linked to proliferation, inflammation, and cancer. RAS is associated with BE dysplasia. The aim of this study is to investigate possible effects of the RAS in BE dysplasia by using RAS‐interfering pharmaceutical agents and by assessment of global protein expression in esophageal mucosal biopsies. Methods: Endoscopic biopsies are taken from 18 BE in patients with low‐grade dysplasia before and after 3 weeks of treatment with either angiotensin‐converting enzyme inhibitors (enalapril 5 mg; n = 6) or angiotensin II receptor type 1 blockers (candesartan 8 mg; n = 6), or no treatment ( n = 6). A global proteomics analysis by 2D gel electrophoresis and mass spectrometry (MS) is then performed to identify proteins that are regulated after interference with RAS. Results: Three proteins are identified to show significant modulation of expression 60 kDa heat shock protein (downregulated), protein disulfide isomerase A3 (downregulated), and inorganic pyrophosphatase (upregulated). Conclusion: Three proteins with no previously known links to esophageal RAS, but with possible relevance for the development of esophageal adenocarcinoma (EAC) are detected. Altered expression by interference with the RAS suggests an involvement of angiotensin II in the development of EAC in BE.